'Good' and 'Bad' deaths during the COVID-19 pandemic: insights from a rapid qualitative study. Issue 6 (1st June 2021) - Simpson, Nikita; Angland, Michael; Bhogal, Jaskiran K; Bowers, Rebecca E; Cannell, Fenella; Gardner, Katy; Gheewala Lohiya, Anishka; James, Deborah; Jivraj, Naseem; Koch, Insa; Laws, Megan; Lipton, Jonah; et al.
Abstract : Dealing with excess death in the context of the COVID-19 pandemic has thrown the question of a 'good or bad death' into sharp relief as countries across the globe have grappled with multiple peaks of cases and mortality; and communities mourn those lost. In the UK, these challenges have included the fact that mortality has adversely affected minority communities. Corpse disposal and social distancing guidelines do not allow a process of mourning in which families and communities can be involved in the dying process. This study aimed to examine the main concerns of faith and non-faith communities across the UK in relation to death in the context of the COVID-19 pandemic. The research team used rapid ethnographic methods to examine the adaptations to the dying process prior to hospital admission, during admission, during the disposal and release of the body, during funerals and mourning. The study revealed that communities were experiencing collective loss, were making necessary adaptations to rituals that surrounded death, dying and mourning and would benefit from clear and compassionate communication and consultation with authorities.